Measurement of Ωc0 baryon production and branching-fraction ratio BR(Ωc0 → Ω-e+νe)/BR(Ωc0 → Ω-π+) in pp collisions at √s=13 TeV - Acharya, S.; Adamova, D.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; et al. (AMER PHYSICAL SOC, 2024)
The inclusive production of the charm-strange baryon Omega(0)(c) is measured for the first time via its semileptonic decay into Omega(-)e(+)nu(e) at midrapidity (vertical bar y vertical bar Omega(-)e(+)nu(e))/BR(Omega(0)(c) -> Omega(-)pi(+)) is measured to be 1.12 +/- 0.22 (stat) +/- 0.27 (syst). Comparisons with other experimental measurements, as well as with theoretical calculations, are presented.
Keywords: PROTON-PROTON; DECAYS; D-0; Astronomy & Astrophysics; Physics